Optimalisasi Penatausahaan Aset Tetap Berupa Tanah Dalam Meningkatkan Akuntabilitas Laporan Keuangan Di Kabupaten Jayawijaya - Tumija, Tumija; Kogoya, Yanechson Gwarry; Agustina, Ika (JEKP (Jurnal Ekonomi dan Keuangan Publik), 2024)
Papua is an area where problems often arise regarding land ownership rights. One of them is in Jayawijaya Regency, where there are still frequent cases of land disputes, especially land owned by the Jayawijaya Regency Government. This issue regarding the legality of land belonging to the Jayawijaya Regency government will greatly influence the administration of land assets, because the assets recorded must have strong evidence of legality such as land certificates. Therefore, the Jayawijaya Regency Government must optimize the administration of fixed assets in Jayawijaya Regency, especially land assets. The aim of this research is to determine the optimization of the administration of fixed assets in the form of land in increasing the accountability of financial reports carried out by the Regional Financial and Asset Management Agency of Jayawijaya Regency. The research method used is descriptive qualitative. Researchers used observation, interview and documentation techniques. The data that has been collected is then analyzed by collecting data, analyzing the data, and drawing conclusions. The research results obtained show that the administration of land assets is not optimal, namely because there are still problems in securing assets and human resources within the Jayawijaya Regency BPKAD environment. In this case, the steps taken by BPKAD Jayawijaya Regency are to increase asset security and improve the quality of human resources through providing training and technical guidance